2020
DOI: 10.1097/brs.0000000000003448
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Patient Characteristics Commonly Captured Before Surgery Do Not Accurately Predict Long-Term Outcomes of Lumbar Microdiscectomy Followed by Physiotherapy

Abstract: Supplemental Digital Content is available in the text Prognostic models for recovery, pain, and disability following lumbar microdiscectomy and postoperative physiotherapy were developed and internally validated. The models performed poorly. Currently gathered data do not enable surgeons and clinicians to predict the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The derivation and internal validation of the prognostic models revealed that the explained variance scored poorly, and the discriminative ability was poor to acceptable. This is in line with previous research on prediction models for lumbar microdiscectomy [8,10,26,38]. The role of potentially important biomedical factors (e.g., degeneration, type of disc herniation) and psychosocial factors (e.g., distress, depression, or fear-avoidance) should be further explored [3,5,9,10,40].…”
Section: Discussionsupporting
confidence: 85%
“…The derivation and internal validation of the prognostic models revealed that the explained variance scored poorly, and the discriminative ability was poor to acceptable. This is in line with previous research on prediction models for lumbar microdiscectomy [8,10,26,38]. The role of potentially important biomedical factors (e.g., degeneration, type of disc herniation) and psychosocial factors (e.g., distress, depression, or fear-avoidance) should be further explored [3,5,9,10,40].…”
Section: Discussionsupporting
confidence: 85%
“…Other social factors known to be associated with musculoskeletal disorders including income and place of residence were not available in the QOD [ 60 , 61 ]. These data are especially important in light of recent work indicating that outcomes following microdiscectomy could not be accurately predicted by commonly captured sociodemographic variables [ 62 ]. It is unknown how including additional SDoH would affect the present results.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen studies [35,38,39,43,45,46,48,49,55,57,59,63,64,66] did not adjust their final models for age, gender, or baseline pain severity (Table 2). showed a small association between the female sex and persistent leg pain after lumbar microdiscectomy (OR = 1.15, 95% CI = 0.63 to 2.08) (Figure 2).…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Two of these factors, opioid use before surgery and legal representation at the time of surgery, met our criteria as promising for future investigations (Table 6). [53] Udby et al [66] En'Wezoh et al [38] Willems et al [63] Two out of six studies showed that higher One study out of the two studies showed a significant association between passive coping with functional limitations/disability [49] Than et al [55] One out of three studies showed that higher preoperative quality was associated with a higher probability of sustaining RTW which we could not perform a meta-analysis. Another limiting factor that precluded us from a meta-analysis of most variables was incomplete data reporting, such as many studies only reported p-values [38,46,57] or SE [36] or OR without 95% CI [44] or only beta-coefficient [49,53].…”
Section: Rtw = Return To Workmentioning
confidence: 99%